Smart Contract: Theoretical Basis and Application Dialectic - Othman, Ayman (Journal of Legal Sciences, 2023)
This study focuses on the relationship of the smart contracts and legal application in the field of civil and commercial contracts. The study aimed to anticipate the possibility of issuing a new law in the future, Nowadays, smart contracts t is a legal challenge that cannot be ignored, Despite the UAE legislator’s interest in artificial intelligence technologies and studying them from the legislative aspect, especially in the field of self-driving cars and the use of robots, and looking forward to a global leadership in the field of Block chain, it is still early to talk about bringing the Block chain to the ground of legislative reality in light of the challenges and risks arising from many challenges that We discussed them in this comparative study with international trends towards the legality of the work of the block chain. To clarify this issue, we write this research paper in order to discuss the challenges and legal difficulties, Therefore, this prompted us to focus more on applying Blockchain technology to law and transactions more precisely. This led me to pose the problem of the appropriateness of current legislation to accommodate Blockchain technology and the legal problems that it can cause on a realistic level. In addition to the availability of confidence and security to accelerate the legislative pace in the Blockchain to keep pace with the developments of what (Blockchain) offers in our contemporary legal life. we made recommendations aimed at addressing these legal challenges to contribute to addressing them.